Models and theories that can guide grief and bereavement information interventions: an information behaviour lens - Ina Fourie (Information Research: An International Electronic Journal)
Introduction. Information behaviour in grief, bereavement, death, dying and its influence on the development of information interventions is understudied. Although pragmatic and evidence-based practices work well, theoretical and conceptual models, research findings and theories should inform grief and bereavement information interventions developed by specialist counsellors. Extensive literature on death, dying, grief and bereavement counselling/therapy and information behaviour per se, does not address this need. This paper reports on work in progress exploring existing theories and models that might guide research.